Clinical impact of diabetes mellitus in patients hospitalized for myocardial infarction. (25th November 2020) - Schmitt, V.H; Hobohm, L; Munzel, T; Wenzel, P; Gori, T; Keller, K
Abstract: Background: Diabetes mellitus (DM) represents a major cardiovascular risk factor for coronary artery disease and myocardial infarction (MI). Purpose: We aimed to assess in-hospital events and time trends in MI patients with and without DM between 2005 and 2016 in Germany. Methods: The nationwide German inpatient sample 2005–2016 was used for statistical analysis (source: Research Data Center (RDC) of the Federal Statistical Office and the Statistical Offices of the federal states, DRG Statistics 2005–2016, own calculations). Hospitalized MI patients were stratified for the presence of DM and the impact of DM on in-hospital events was investigated. Results: A total of 3, 307, 703 patients with acute MI (37.6% females, 56.8% aged ≥70 years) were included in the present analysis. Of these, 1, 007, 326 (30.5%) patients were coded for additional DM. More MI patients with DM were female (41.2% vs. 36.0%, P<0.001) and aged 70 years or older (64.3% vs. 53.5%, P<0.001). Presence of most cardiovascular risk factors was increased in coprevalence with DM compared to non-diabetics (obesity: 14.1% vs. 7.2%, essential arterial hypertension: 60.9% vs. 52.4%, hyperlipidaemia 40.5% vs. 37.8%, P<0.001), only smoking was more frequent in people without DM (4.8% vs. 8.5%, P<0.001). Additionally, DM was associated with an elevated occurrence of comorbidities like peripheral artery disease (10.8% vs. 4.5%, P<0.001), atrial fibrillation/flutter (26.5% vs. 19.6%, P<0.001) and acute or chronic kidney disease (39.8% vs. 21.8%, P<0.001). Recurrent MI events during the first 4 weeks after previous MI were more common in MI patients with DM (0.8% vs. 0.6%, P<0.001). Pneumonia (14.9% vs. 10.2%, P<0.001), acute kidney injury (8.6% vs. 5.2%, P<0.001) and stroke (3.4% vs. 2.7%, P<0.001) were more prevalent in MI patients with DM. Mortality was significantly increased in patients with DM (13.2% vs. 12.1%, P<0.001). While the proportion of MI patients with DM increased slightly from 29.8% in 2005 to 30.7% in 2016 (β 7.04 [95% CI 4.13–9.94], P<0.001), the in-hospital mortality rate of MI patients with DM decreased substantially from 15.2% in 2005 to 11.5% in 2016 (β −0.36 [95% CI: −0.38 to −0.34], P<0.001). Confirming this results, the univariate logistic regression analyses demonstrated that DM was associated with a higher in-hospital mortality (OR 1.1 [95% CI: 1.1–1.1], P<0.001), higher risk for recurrent MI (OR 1.3 [95% CI: 1.3–1.4], P<0.001), and higher frequency of acute kidney injury (OR 1.7 [95% CI: 1.7–1.7], P<0.001). Conclusions: While the proportion of MI patients with DM increased only slightly from 2005 to 2016, the in-hospital mortality decreased substantially in MI patients with DM. DM was associated with an aggravated cardiovascular risk profile, higher prevalence of comorbidities and increased in-hospital mortality during hospitalization. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study was supported by the German Federal Ministry of Education and Research (BMBF 01EO1503); institutional grant for the Center for Thrombosis and Hemostasis.